Wave of the sea dragon - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters, 2021)
Drake and the other Dragon Masters go to the island of Kapua seeking a Sea Dragon needed to help stop the evil wizard Astrid's dangerous False Life spell.